Alterations of circulating bacterial DNA in colorectal cancer and adenoma: A proof-of-concept study. (28th February 2021) - Xiao, Qian; Lu, Wei; Kong, Xiangxing; Shao, Yang W.; Hu, Yeting; Wang, Ao; Bao, Hua; Cao, Ran; Liu, Kaihua; Wang, Xiaonan; Wu, Xue; Zheng, Shu; et al.
Abstract: The gut microbiota is closely associated with colorectal neoplasia. While most metagenomics studies utilized fecal samples, circulating bacterial DNA in colorectal neoplasia patients remained unexplored. This proof-of-concept study aims to characterize alterations of circulating bacterial DNA in colorectal neoplasia patients. We performed WGS of plasma samples from 25 colorectal cancer (CRC) patients, 10 colorectal adenoma (CRA) patients and 22 healthy controls (HC). Bacterial relative abundance was measured by removing the host genome and mapping reads into bacterial genomes. By diversity analysis, we found plasma samples required less sample size to approach saturation than fecal samples, and species diversity in HC was slightly higher compared with CRC/CRA patients. The majority of circulating bacterial DNA came from bacterial genera which commonly associated with gastrointestine and oral tract. By differential analysis, a total of 127 significant species between CRC patients and HC were identified, on which basis 28 species with top predictive ability were selected and showed promise in preliminary discrimination between CRC/CRA and HC. In CRA patients, relative abundance of the selected 28 species more closely resembled those in CRC patients than HC. By comparing with fecal metagenomics studies, we found there was moderate positive correlation between fold changes of the overlapped fecal and circulating bacterial DNA. Finally, species correlation analysis revealed that CRC and HC displayed distinct patterns of species association. In conclusion, this study demonstrated alterations of circulating bacterial DNA in colorectal neoplasia patients, which had the potential to become non-invasive biomarkers for colorectal neoplasia screening and early diagnosis. Highlights: This pioneer study characterized alteration of circulating bacterial DNA in patients with colorectal neoplasia. The majority of circulating bacterial DNA may come from gastrointestine and oral tract. The selected 28 bacterial species had potential to distinguish colorectal neoplasia patients from healthy individuals. Colorectal cancer and healthy individuals displayed distinct patterns of circulating bacterial species association.